Usulan Peningkatan Keselamatan Kerja Operator Produksi Melalui Metode Job Safety Analysis di CV XYZ - Syalina Amalia; Mochammad Ariq Farizi; Yoga Rizki Fadilah; Rico Ferdinand Alhakim; Yuniar Yuniar (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study aims to identify potential hazards, assess occupational safety risk levels, determine the root causes of dominant risks, formulate control recommendations, and develop an occupational safety dashboard for the knife production process at CV XYZ. The study employs an empirical approach through field observations and interviews, while activity mapping is conducted using an Operation Process Chart. Hazard identification and risk assessment were conducted using a Job Safety Analysis with a Probability Severity matrix; subsequently, the activities with the highest risks were analyzed using the 5 Whys Analysis. The results showed that of the 17 activities evaluated, 4 were categorized as Low Risk, 12 as Medium Risk, and 1 as High Risk specifically, the heat treatment process, which had a Risk Number of 12. The root cause analysis identified the lack of safety signs and communication materials regarding the use of personal protective equipment as the dominant causes of increased workplace accident risk. Control recommendations include installing safety signs, posting notices regarding the mandatory use of personal protective equipment, and providing heat-resistant gloves, safety goggles, and heat-resistant safety shoes. All research findings are integrated into an OSH dashboard built on Google Looker Studio, which presents risk information, safety indicators, PPE requirements, and cost analyses to support data-driven decision-making aimed at improving the effectiveness of workplace safety management.